A longitudinal study of sentence comprehension difficulty in primary progressive aphasia. Issue 5 (15th April 2005) - Grossman, M; Moore, P
Abstract : Context: Patients with primary progressive aphasia have sentence comprehension difficulty, but the longitudinal course of this deficit has not been investigated. Objective: To determine how grammatical, single word meaning, and working memory factors contribute to longitudinal decline of sentence comprehension in primary progressive aphasia. We hypothesised partially distinct patterns of sentence comprehension difficulty in subgroups of patients with progressive non-fluent aphasia (PNFA) and semantic dementia (SD). Design: Cohort. Setting: Institutional out patient referral centre. Patients: PNFA (n = 14), SD (n = 10). Main outcome measure: Sentence comprehension accuracy. Results: PNFA patients were significantly impaired at understanding grammatically complex sentences when first seen, and this was more evident than impairment of their comprehension of grammatically simple sentences (p<0.05). Comprehension of grammatically complex sentences correlated with their working memory deficit at presentation (p<0.05). PNFA patients showed modest decline over time in grammatical comprehension. In SD, comprehension of grammatically complex sentences was not more impaired than comprehension of grammatically simple sentences when first seen, but these patients demonstrated a significant longitudinal decline in understanding grammatically complex sentences (p<0.05). Cox regression analyses showed that a deficit in single word meaning contributes to the progressive impairment for grammatically complex sentences in SD (p<0.05), but working memory does not contribute to longitudinal decline in PNFA. Conclusion: Patients with PNFA and SD have sentence comprehension difficulty, but distinct factors contribute to this impairment during the course of their disease.